Efektifitas Program Pemutakhiran Data Kependudukan dalam Pelayanan Penerbitan NIK di Kecamatan Sebatik Tengah - Hasnah; Dandan Haryono; Agus Priyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to describe and analyze the extent to which the issuance of NIK (National Identification Number) services through population data updates in Central Sebatik District, Nunukan Regency, as well as the supporting and inhibiting factors in the implementation of this program. This research employs a descriptive qualitative research design (positivism) with a quasi-qualitative format. The quasi-qualitative format was chosen due to the relatively short time frame in which the research was conducted, resulting in the collection of simple qualitative data, which was then analyzed descriptively to obtain answers to the research questions. In the data collection process, this research uses interview methods and literature/documentary studies to provide an overview of the implementation of NIK issuance services through population data update programs, particularly for residents aged 5 years and 3 months and above. This study uses the effectiveness theory proposed by Budiani to measure the effectiveness of this program using four dimensions: target accuracy, socialization, goal achievement, and program monitoring. The results of this study indicate that the implementation of NIK issuance services through population data updates for residents aged 5 years and 3 months and above is still not effective. This conclusion is based on an analysis through the effectiveness dimensions, which did not meet the expected results. The dimension of target accuracy of this program has been very good in reaching all villages in the Central Sebatik District area, but the other three dimensions are still not optimal. This is influenced by several supporting and inhibiting factors in the implementation of the program. Supporting factors include the delegation of authority from the Regent to the Sub-District Head and excellent collaboration among stakeholders in the Central Sebatik District area in overcoming emerging obstacles. Inhibiting factors include limited sub-district budget, inadequate quality and quantity of human resources in both sub-district and village governments, and the presence of residents who do not have basic documents proving their Indonesian citizenship.